2018
DOI: 10.3389/fpls.2018.01234
|View full text |Cite
|
Sign up to set email alerts
|

Increased DHA Production in Seed Oil Using a Selective Lysophosphatidic Acid Acyltransferase

Abstract: Metabolic engineering of the omega-3 (ω3) long chain polyunsaturated fatty acid biosynthesis pathway has generated fish oil-like levels of pharmaceutically and nutritionally important docosahexaenoic acid (DHA) in plant seeds. However, the majority of DHA has been accumulated at the sn-1 and sn-3 positions of triacylglycerol (TAG) in these engineered seeds, leaving only a minor amount (∼10%) at sn-2 position and indicating a strong discrimination (or, a very poor specificity) for DHA by seed lysophosphatidic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…These fatty acids are intermediates in the metabolic pathway we have used to produce DHA in this study. For example, the use of different versions of the GA7 construct may yield fish oil-like levels of EPA and even higher levels of the relatively rare fatty acid DPA, or possibly further increase the amount of DHA that can be produced in canola seed (Shrestha et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These fatty acids are intermediates in the metabolic pathway we have used to produce DHA in this study. For example, the use of different versions of the GA7 construct may yield fish oil-like levels of EPA and even higher levels of the relatively rare fatty acid DPA, or possibly further increase the amount of DHA that can be produced in canola seed (Shrestha et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, acyltransferases such as diacylglycerol acyltransferase and phospholipid:diacylglycerol acyltransferase have been successfully coexpressed with FA modification enzymes and have rescued defective embryos (Li et al ., 2012; Bates et al ., 2014; Lunn et al ., 2018). LPAT is known as a valuable acyltransferase that exhibits various abundant substrate preferences in different species (Knutzon et al ., 1999; Nath et al ., 2009; Yu et al ., 2014; Kim et al ., 2015; Shrestha et al ., 2018). In the present study we found that CsLPAT2 could rescue our defective embryo phenotype, a result that will provide more options for the production of UFAs in crops in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the M . alpina LPAAT increases sn -2 DHA in seed oil, which was confirmed by both lipase digestion and 13 C NMR [ 26 ]. Nevertheless, a more sensitive and convenient analytical method to quickly screen for and quantify sn -2 DHA will greatly aid characterization of DHA-containing glycerolipids and functional analysis of LPAATs that can increase sn -2 DHA in seed oils.…”
Section: Introductionmentioning
confidence: 85%
“…In vitro measurement of LPAAT enzyme activity is challenging; eukaryote LPAATs are bound to the ER membrane or to the thylakoid membrane of the plastid [ 44 ]. Typically, measurements of LPAAT activity are performed with a heterogeneous microsomal preparation, containing either heterologously expressed protein [ 26 , 45 47 ] or natively expressed protein [ 21 , 27 , 46 , 48 ]. To mitigate background acyltransferase activity, the slc1Δ or ale1Δ (also referred to as slc4Δ ) yeast mutants lacking LPAAT have been used to heterologously express plant acyltransferase proteins [ 49 ].…”
Section: Discussionmentioning
confidence: 99%